Waiting for chikungunya fever in Argentina: Spatio-temporal risk maps - Carbajo, Anibal Eduardo (2015)
Chikungunya virus (CHIKV) transmission has been detected in America in 2013 and recently reached south up to Bolivia, Brazil and Paraguay, bordering countries of Argentina. The presence of the mosquito Aedes aegypti in half of the country together with the regional context drove us to make a rapid assessment of transmission risk. Temperature thresholds for vector breeding and for virus transmission, together with adult activity from the literature, were mapped on a monthly basis to estimate risk. Transmission of chikungunya by Ae. aegypti in the world was seen at monthly mean temperatures from 21-34ºC, with the majority occurring between 26-28ºC. In Argentina temperatures above 21ºC are observed since September in the northeast, expanding south until January and retreating back to the northeast in April. The maximum area under risk encompasses more than half the country and around 32 million inhabitants. Vector adult activity was registered where monthly means temperatures exceeded 13ºC, in the northeast all over the year and in the northern half from September-May. The models herein proposed show that conditions for transmission are already present. Considering the regional context and the historic inability to control dengue in the region, chikungunya fever illness seems unavoidable.